Implications of a Chr7q21.11 Microdeletion and the Role of the PCLO Gene in Developmental Delay - Mazzaschi, Roberto L. (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2013)
We report here a 4-year-old boy with global developmental delay who was referred for karyotyping and fragile X studies. A small interstitial deletion on chromosome 7 at band 7q21 was detected in all cells examined. Subsequent molecular karyotype analysis gave the more detailed result of a 6.3 Mb heterozygous deletion involving the interstitial chromosome region 7q21.11. In this relatively gene-poor region, the presynaptic cytomatrix protein, Piccolo (PCLO) gene appears to be the most likely candidate for copy number loss leading to a clinical phenotype. G-banded chromosome analysis of the parents showed this deletion was inherited from the father. Molecular karyotype analysis of the father’s genome confirmed that it was the same deletion as that seen in the son; however, the father did not share the severity of his son’s phenotype. This cytogenetically-visible deletion may represent another example of a chromosomal rearrangement conferring a variable phenotype on different family members.